Combination of Isoflurane and Propofol as General Anesthesia During Orthopedic Surgery of Perioperative Cerebral Hypoperfusion Rats to Avoid Cognitive Impairment - Bu, Xinyue; Li, Tang; Wang, Haiyun; Xia, Zhengyuan; Guo, Di; Wang, Jinxin; Sun, Yi; Yang, Chenyi; Liu, Guoqiang; Ma, Ji; Yang, Zhuo; Wang, Guolin (Frontiers in Medicine, 2020)
Background: Perioperative cerebral hypoperfusion (CH) is common, although the underlying mechanism of cognitive impairment that results due to perioperative cerebral hypoperfusion remains to be determined. Isoflurane anaesthesia induces neuronal injury via endoplasmic reticulum (ER) stress, whereas a sub-anaesthetic dose of propofol improves postoperative cognitive function. However, the effects of the combination of isoflurane plus propofol, which is a common aesthetic combination administered to patients, on ER stress and cognition remain unknown. Methods: We sought to determine the effects of isoflurane plus propofol on ER stress and cognitive function in rats insulted by cerebral hypoperfusion. Ligation of the bilateral common carotid arteries (CCA) was adopted to develop the cerebral hypoperfusion rat model. A second surgery, open reduction and internal fixation (ORIF), requiring general anaesthesia, was performed 30 days later so that the effects of anaesthetics on the cognitive function of CH rats could be assessed. Rats received isoflurane alone (1.9%), propofol alone (40 mg·kg-1·h-1) or a combination of isoflurane and propofol (1% and 20 mg·kg-1·h-1 or 1.4% and 10 mg·kg-1·h-1). Behavioural studies (contextual fear conditioning [FC] test), histological analyses (Nissl staining) and biochemical analyses (western blotting of the harvested rat brain tissues) were employed. Results: Hippocampus-dependent memory of rats in group IP1 (1% isoflurane plus 20 mg·kg-1·h-1 propofol) was not impaired, and expression level of γ-aminobutyric acid A type receptor α1 subunit, a key cognition-related protein, remained normal. ER stress alleviator, binding immunoglobulin protein, increased extremely while ER stress transcription factor, C/EBP homologous protein, showed no statistical difference compared with the control group. Numbers of surviving neurons confirmed the substantial neuronal damage caused by propofol or isoflurane alone. Conclusions: These data suggest that ER stress contributes to the underlying mechanism of cognitive impairment and that the combination of isoflurane and propofol did not aggravate cognitive impairment and ER stress in ageing rats with CH that were further subjected to ORIF surgery.